The Effect of Pranayama Yoga Exercise on Erythrocyte Sedimentation Rate (ESR) in Adolescent Girls with Primary Dysmenorrhea - Mayani, Widya; Rosyida, Desta Ayu Cahya; Solichatin, Solichatin; Rihardini, Tetty (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2026)
Dysmenorrhea is a common menstrual disorder experienced by adolescent girls and may trigger an inflammatory response in the body, as indicated by an increased erythrocyte sedimentation rate (ESR). One non-pharmacological intervention that may help alleviate this condition is yoga pranayama. This study aimed to analyse the effect of yoga pranayama on reducing ESR levels in adolescents with dysmenorrhea. This study used a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 31 adolescent girls experiencing dysmenorrhea. The yoga pranayama intervention was conducted over 4 weeks, comprising 8 sessions, each lasting 30 minutes. ESR measurements were obtained before and after the intervention using the Westergren method, and the data were analysed using the Wilcoxon signed-rank test. The results showed a decrease in ESR levels after the intervention, with 48.4 percent of respondents categorised as normal (10–20 mm/h), although 51.6 percent remained in the high category (more than 20 mm/h). Statistical analysis indicated a significant difference between pretest and posttest ESR values. This reduction is associated with the relaxation effects of yoga pranayama, which improve tissue oxygenation, enhance blood circulation, and reduce inflammatory responses caused by increased prostaglandins. In conclusion, yoga pranayama is an effective non-pharmacological therapy for reducing ESR in adolescents with dysmenorrhea.